2016
DOI: 10.1111/jir.12331
|View full text |Cite
|
Sign up to set email alerts
|

Route‐learning strategies in typical and atypical development; eye tracking reveals atypical landmark selection in Williams syndrome

Abstract: The current results demonstrate that attention to landmarks during route learning reflects the types of landmarks remembered in memory tasks, that individuals with WS can learn a route if given sufficient exposure, but that this is accomplished within the context of an impaired ability to select appropriate landmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Nardini, Atkinson, Braddick, & Burgess (2008) showed that WS children showed a poor and anomalous pattern in using different frames of reference to recall the location of a hidden object. Similar anomalies have been found in locating objects in larger-scale space (Mandolesi et al, 2009) and in the spatial reference frames and strategies used by WS children for navigation (e.g., Broadbent, Farran, & Tolmie, 2014; Farran, Formby, Daniyal, Holmes, & Van Herwegen, 2016). …”
Section: Introductionsupporting
confidence: 58%
“…Nardini, Atkinson, Braddick, & Burgess (2008) showed that WS children showed a poor and anomalous pattern in using different frames of reference to recall the location of a hidden object. Similar anomalies have been found in locating objects in larger-scale space (Mandolesi et al, 2009) and in the spatial reference frames and strategies used by WS children for navigation (e.g., Broadbent, Farran, & Tolmie, 2014; Farran, Formby, Daniyal, Holmes, & Van Herwegen, 2016). …”
Section: Introductionsupporting
confidence: 58%
“…It is highly possible that there is a difference in the ability of individuals with WS to show an effect of a given spatial frame of reference, compared to being able to select a useful frame of reference (and to use it effectively). Recent evidence has demonstrated that individuals with WS often select inappropriate landmarks when navigating (Farran et al, 2016); this tentatively supports the notion that the ability to select an appropriate frame of reference is impaired in WS.…”
Section: Discussionsupporting
confidence: 55%
“…The data described in both our studies with walking RAM task (Mandolesi et al, 2009a ) and table RAM task highlight that in WS the deficit in the elaboration of the allocentric space is different from that in the peripersonal space. While in the elaboration of the peripersonal space the WS individuals exhibited memory but not procedural deficits, in the elaboration of the allocentric space they exhibited, beside the memory deficit, also remarkable procedural deficits (Mandolesi et al, 2009a ; Farran et al, 2012 , 2016 ; Foti et al, 2013 ; Broadbent et al, 2014b ). Such diversity of processing of near and far space may be explained by taking into account the sensorimotor and cognitive processes recruited as well as the neuronal circuitry involved in the two conditions.…”
Section: Discussionmentioning
confidence: 97%